Notes on the identities of the new genera and species published by Domenico (Domingos) Vandelli in the Florae Lusitanicae et Brasiliensis specimen - de Moraes, Pedro Luís Rodrigues [UNESP] (Wiley, 2019)
The Florae Lusitanicae et Brasiliensis specimen, published in 1788, is revisited here after encountering three manuscripts that proved to be directly related to the new genera described by Domenico Vandelli. One of them is a bound folio of watercolor drawings with 133 plates containing sketches of branches, inflorescences and/or fruits of each species, as well as drawing of dissections of their flowers and/or fruits. Those drawings had been copied from original material collected and sent to Portugal from Brazil by Joaquim Vellozo de Miranda. Vandelli used them as the basis for his descriptions of new Brazilian taxa. Examinations of the drawings have allowed the identification of 21 new genera (most of them to the species level) out of 25, thus clarifying the taxonomic status of several taxa that had remained unresolved since the 1788 publication date. A significant nomenclatural discovery is that Tapanhuacanga Vand. has now been shown to be Psyllocarpus laricoides Mart. & Zucc. Therefore, Tapanhuacanga has priority over Psyllocarpus, which has required 12 new combinations undertaken here. Three new synonymies, typification of five genera and 18 lectotypifications are proposed.
Keywords: Joaquim Vellozo de Miranda; Minas Gerais; nomenclature; Psyllocarpus; Tapanhuacanga; taxonomy